Pengaruh Kolaborasi Model Pembelajaran Think Pair Share dan Aplikasi Quizizz terhadap Minat Belajar dan Pemahaman Konsep Siswa Kelas VIII SMP pada Materi Sistem Ekskresi - TheresiaUto Tukan; Yoseph Tuta Mago, Oktavius (Jurnal Biogenerasi, 2025)
The purpose of this study was to determine the effect of combining the Think Pair Share (TPS) learning model with the Quizizz application on students’ learning interest and conceptual understanding in the topic of the excretory system. The research was conducted at SMP Negeri 3 Maumere using a quantitative approach and a pre-experimental method, specifically a One-Group Pretest-Post-test Design. The sample consisted of 20 students from class VIII B. Instruments used for data collection included a pretest, post-test, and a questionnaire. The pretest results showed an average score of 35.00, which increased to 88.25 in the post-test. Students’ learning interest also demonstrated a significant improvement, with an average percentage of 89.125%, categorized as very good. Statistical analysis using the Paired Sample T-Test revealed a significance value of < 0.001, indicating a substantial effect of the TPS learning model and Quizizz application on students’ learning interest and conceptual understanding. The study concluded that the combination of TPS and Quizizz is an effective learning strategy that fosters an active, enjoyable learning process while enhancing student engagement and understanding.